Fundamental study on the sounds of standard Baltic languages: phonetic and phonological differences - Jaroslavienė, Jurgita; Urbanavičienė, Jolita (Lietuvių kalba, 2020)
The article discusses the most important differences in the sound structure of contemporary Lithuanian and Latvian standard languages, scientific and practical benefits of a fundamental comparative instrumental sound research, reviews possible further innovations in theories and methods of acoustic and articulatory phonetics and phonology, and perspectives as well as tasks of such research. In his monograph Comparative History of the Baltic Languages (2019), Pietro Umberto Dini observes that there is a constant decline in the synthetic structure in the Baltic language systems, most notably as a reduction of the flexural forms of the noun and verb. He argues that the Baltic languages, like all other Indo-European languages, recognise a structural development: agglutination → synthetic → isolation language. According to the author, the isolation stage of development in the Lithuanian language is just starting, and the isolation structure of the Latvian language is becoming more and more pronounced. Pietro Umberto Dini states that “from the Baltic systems, the Latvian language ‘drifts’ faster in terms of structural development, and the Lithuanian language remains the most morphologically conservative of the current Indo-European languages due to the much slower change” (Dini 2019, 577). The author, based on, for example, the growing tendency in the colloquial Lithuanian language to move the accent to the first syllable (where the accent has long been emphasised in the Latvian language), considers that analogous tendencies are observed in both languages, i.e. the Baltic languages are evolving towards convergence. The data presented in this article and the latest synchronous instrumental studies of the sounds of the Baltic languages do not confirm the convergence trends: the sound structure of the Lithuanian and Latvian languages is still quite different (cf. Urbanavičienė, Indričāne, Jaroslavienė, Grigorjevs 2019, 286; see also Jaroslavienė, Grigorjevs, Urbanavičienė, Indričāne 2019). Both Baltic languages are characterised by quantitative vowel opposition, adjective system (polytonicity), sufficiently simple structure of consonant compounds (e.g. CV and CVC syllable types make up 79% of all Lithuanian syllables, see Karosienė, Girdenis 1994, 40), the same phonological opposition of consonants (voting, modal, local). However, the Lithuanian language has a free accent, while the Latvian language has a fixed accent. One of the most important distinguishing features of the current Baltic languages is palatalization: Lithuanian language is characterised by secondary palatalization and opposition palatalised vs. unpalatalised realisation, which presupposes a twice as large inventory of consonant phonemes in the Lithuanian language and, in comparison with the Latvian language, an accurate, precise articulation of consonants. The article highlights certain similarities and differences in the sound structure of the contemporary Lithuanian and Latvian standard languages based on the latest synchronous comparative research of the Baltic sound system: two scientific monographs of the series Sounds of the Baltic Languages in the early 21st Century (Jaroslavienė, Grigorjevs, Urbanavičienė, Indričāne 2019; Urbanavičienė, Indričāne, Jaroslavienė, Grigorjevs 2019), where the sounds of Lithuanian and Latvian languages are instrumentally studied and described according to the same principles. This is an excellent basis to continue the instrumental study of the contemporary Baltic sounds (and to discuss the importance of the research) on other relevant aspects and perspectives (a few new instrumental non-comparative studies already exist, cf. Ledichova 2020); to update and highlight the practical benefits of such studies and audio recordings (by taking into account the assistance in language learning, examining standard language norms, pronunciation tendencies, the importance in medicine, developing tools and instruments for language technology and artificial intelligence), innovations and perspectives of theories and methods. It is a very important incentive to continue instrumental scientific and practical research of Lithuanian sound methodological innovations, drawing increasingly clear prospects for further research.